2020
DOI: 10.1038/s41598-020-60077-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis of Bacillus subtilis extracellular vesicles through an in vitro intestinal epithelial cell model

Abstract: Bacterial eVs have been related to inter-kingdom communication between probiotic/pathogenic bacteria and their hosts. our aim was to investigate the transcytosis process of B. subtilis eVs using an in vitro intestinal epithelial cell model. In this study, using Confocal Laser Scanning Microscopy, we report that uptake and internalization of cfSe-labeled B. subtilis EVs (115 nm ± 27 nm) by Caco-2 cells are time-dependent. to study the transcytosis process we used a transwell system and eVs were quantified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…While the current paper was in preparation, two recent reports found similar results in gram-positive non-pathogenic bacteria. Rubio and colleagues found that Bacillus subtilis MV were internalized and apparently transcytosed by Caco-2 cells in vitro 30 , while Bajic and colleagues demonstrated that MV from Lactiplantibacillus plantarum BGAN8 are endocytosed by HT-29 cells in a clathrin-dependent manner 31 .…”
Section: Discussionmentioning
confidence: 99%
“…While the current paper was in preparation, two recent reports found similar results in gram-positive non-pathogenic bacteria. Rubio and colleagues found that Bacillus subtilis MV were internalized and apparently transcytosed by Caco-2 cells in vitro 30 , while Bajic and colleagues demonstrated that MV from Lactiplantibacillus plantarum BGAN8 are endocytosed by HT-29 cells in a clathrin-dependent manner 31 .…”
Section: Discussionmentioning
confidence: 99%
“…EVs injected intravenously into mice first reached spleen and liver and subsequently distributed to gastrointestinal tract and lungs [105]. Permeation for exosomes across epithelial barriers (e.g., blood-brain barrier, gastrointestinal barrier) has been shown for endogenous and exogenous (Bacillus subtilis-derived) exosomes [106]. The transport is assumed to be better when parental cells and barrier forming cells are similar.…”
Section: Intravenous Versus Inhalation Route Of Delivery Of Mscs and mentioning
confidence: 99%
“…In this context it is worth to speculate whether (O)MVs could actually be transcytosed through the alveolar barrier allowing for infectious dissemination throughout the body. While such mechanisms were not described in the lung yet, it was already shown in the gut that (O)MVs are indeed able to cross epithelial barriers and enter the vascular system [ 77 , 78 ]. On the functional level, OMVs from a variety of lung pathogens including P. aeruginosa , L. pneumophila, A. baumannii , K. pneumoniae , M. catarrhalis, and S. maltophilia can induce the release of proinflammatory mediators from the epithelium.…”
Section: The Interaction Of (O)mvs With the Respiratory Epithelium—a First Step In Immunoactivationmentioning
confidence: 99%